Supratentorial cystic hemangioblastoma with infratentorial extension - a unique location and a rare infant case - (:unkn) unknown (SPRINGER, 2006)
Introduction: Supratentorial occurrence of hemangioblastoma is an exceedingly rare event. Even rarer is the occurrence of a supratentorial hemangioblastoma in infancy. Case report: We hereby report the case of an 18-month-old girl who presented with irritability, increasing head size, and an open fontanelle. MR scans demonstrated triventricular hydrocephalus and a cystic mass within the left lateral ventricle. There was an 18 x 15 x 13 mm enhancing nodule along the medial aspect of the cyst. The cystic mass was mainly supratentorial but there was a caudal extension through the tentorial incisura that compressed the cerebellum. At surgery, the content of the cyst was xanthochromic. Enhancing medial nodule was extremely vascular and was extirpated totally. The pathological diagnosis was reticular variant of hemangioblastoma. Conclusion: The child is well at 4 years of age. An extensive review of the English literature revealed only three such cases. All three cases survived the operation.
Keywords: brain neoplasm; hemangioblastoma; infant; survival; PRIMARY INTRACRANIAL NEOPLASMS; BRAIN-TUMORS; 1ST YEAR; LIFE; CHILDREN; AGE